POLICE IN PERSUASIVE COMMUNICATION STRATEGIES INCREASE THE PARTISPASI SOCIETY AT THE SAFE HOUSE PROGRAM IN DISTRICT SUKAJADI PEKANBARU - Elizabeth Br. Lingga; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Safe House is a program established by the Police Sector Sukajadi. The program is conducted almost three years, and still there from some people who do not know the safe house program. It is also shown that not all the people involved in the safe house program, and the participation of people from year to year has decreased leading to poor public perception of the police. Therefore, this study aims to determine the strategy of persuasive communication on the program safe house of the police, the elements of persuasive communication on the program safe house of the police to improve community participation Sukajadi and communication barriers persuasive police to improve community participation in the programme safe house.This study uses descriptive qualitative data collection techniques of observation, interviews, and documentation. The data obtained are then processed to be reduced, resulting conclusions presented to the public. Mechanical election informants in this study were seven based techniques that researchers use purposive. Data was collected through interviews, observation, and documentation. As for the technical examination of the validity of data, researchers useextension of participation techniques and triangulation.The results showed that (1)strategy of persuasive communication in the program safe house through a strategy of psychodynamic by touching people's emotional, and communicating rampant criminal acts that result in material damage or lead to death the victims, persuasion sociocultural police participated on public activity (2)unsur elements persuasive communication on program safe house through persuader presence of some police personnel were less than friendly, indifferent and only standbay diposguard, persuadee public response to the program open or positive, the message is less effective, the channel used by the delivery of home home (door to door), stickers appeal, as well as direct communication (face to face), the feedback given community is very positive, (3)obstacle-barrier persuasive communication in the program safe house that social status differences in economic status, job title / position in the community, as well as their prejudiced this program only for imaging the police.Keywords: Strategy Persuasive Communication, Safe House, Participation of Public